Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C